Health literacy, resilience and perceived stress of migrants in Israel during the COVID-19 pandemic. Issue 9 (8th August 2022) - Zlotnick, Cheryl; Dryjanska, Laura; Suckerman, Suzanne
Abstract: Objective: To examine perceived stress in migrants guided by Bornstein's Specificity Principle in Acculturation Science (BSPAS) theoretical framework. Design: Using a cross-sectional study, we recruited English-language migrants (n = 411) living in Israel to respond to an online questionnaire during the COVID-19 pandemic, from 3 April to 16 May 2020. Main Outcome Measures: The dependent variable comprised the Perceived Stress Scale (PSS) scores, which attained an internal consistency of 0.91 in this sample. Results: PSS scores were related to lower age (p < 0.0001), being single (p = 0.0095), not possessing high (p = 0.0069) or medium resilience (p = 0.0002), reporting below average SES (p = 0.0196), being "extremely" worried about getting COVID-19 (p < 0.0001), and having high health literacy (p = 0.0007). Additionally, the interaction between health literacy and resilience (p < 0.0001) showed that migrants with high resilience and high health literacy had the lowest perceived stress; and migrants with low resilience and high health literacy had the highest perceived stress. Conclusions: Interventions are needed to assist migrants during the COVID-19 pandemic. The optimal intervention will aim to address the psychological distress while increasing both health literacy and resilience.